Effects of plasma treatment on the shear bond strength between fiberreinforced composite posts and resin composite for core build-up - Yavirach P. (2014)
The aim of this study was to evaluate the effects of plasma treatment on adhesion between fiber-reinforced posts and a composite core material. Two types of posts, methacrylate-based (FRC Postec) and epoxy resin-based (DT Light-Post), were treated with oxygen plasma (O2), argon plasma (Ar), nitrogen plasma (N2), or helium mixed with nitrogen plasma (He+N2) using a radio-frequency generator before bonding to a methacrylate-based composite. Pull-out tests were performed using a universal testing machine. Surface roughness of each group was evaluated using a profilometer. On tensile-shear bond strength, statistical analysis revealed that the type of post, type of plasma treatment, and their interaction significantly influenced the results (p<0.05). Tukey's test revealed significant differences in tensile-shear bond strength between the control and other plasma treatment groups (p<0.05). On surface roughness, Tukey's test revealed significant differences between the control group and the Ar group (p<0.05) with DT Light Post. Plasma treatment appeared to increase the tensile-shear bond strength between post and composite.